2008
DOI: 10.1007/s10750-008-9298-z
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses of aquatic consumers to variations in leaf-litter inputs

Abstract: Terrestrial support of aquatic food webs is becoming well established in the science of ecology. However, while terrestrial subsidies of energy have been shown to exert strong effects on aquatic food webs, it is less clear how variations in these subsidies, via natural or anthropogenic factors, will affect recipient ecosystems. To assess the influence of variations in terrestrial subsidies on an aquatic food web, we manipulated leaf-litter inputs in artificial ponds. Decreasing litter inputs did not affect any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 31 publications
3
33
1
Order By: Relevance
“…Although this result did not support expectations (temporal variability was hypothesized to be lowest in cDOM treatments), it is consistent with previous studies that showed Experimental evidence that subsidy quality affects the temporal variability of recipient… no effect of leaf litter subsidies on zooplankton abundance relative to controls (Rubbo et al 2008) or even showed slight destabilization (Geddes 2004). It is hypothesized that these latter responses may be mediated by the low quality carbon in cDOM (see below) via a trophic pathway and, to some extent, by a non-trophic pathway, through which subsidies affect recipient communities via physical changes of the environment (Geddes 2009;Kelly et al 2014).…”
Section: Discussionsupporting
confidence: 65%
“…Although this result did not support expectations (temporal variability was hypothesized to be lowest in cDOM treatments), it is consistent with previous studies that showed Experimental evidence that subsidy quality affects the temporal variability of recipient… no effect of leaf litter subsidies on zooplankton abundance relative to controls (Rubbo et al 2008) or even showed slight destabilization (Geddes 2004). It is hypothesized that these latter responses may be mediated by the low quality carbon in cDOM (see below) via a trophic pathway and, to some extent, by a non-trophic pathway, through which subsidies affect recipient communities via physical changes of the environment (Geddes 2009;Kelly et al 2014).…”
Section: Discussionsupporting
confidence: 65%
“…At this time, we also added 150 g of recently senesced and dried leaves to all mesocosms except the no-litter control. This biomass of litter is within the range observed in natural wetlands (Rubbo et al 2008). The mesocosms overwintered until the start of the experiment in the spring.…”
Section: Methodssupporting
confidence: 77%
“…Melody and Richardson (2004) found that a 75% reduction in litter inputs to experimental mesocosms resulted in differences in invertebrate densities, suggesting food limitation. Rubbo et al (2008) also found that variations in leaf litter inputs can affect the structure of aquatic food webs in artificial ponds and that increasing the quantity of leaf litter can positively influence the productivity of amphibian larvae, also providing evidence that suggests food limitation by reduced leaf litter. Further studies would be useful to determine to what extent a reduction in deciduous leaf litter inputs to streams would invoke invertebrate community responses as a result of food limitation and to determine if a threshold of leaf litter loading to boreal forest streams exists.…”
Section: Management Implicationsmentioning
confidence: 84%